Analisis SWOT dalam Identifikasi Mutu Suatu Lembaga Pendidikan - Makmur Syukri; Nur Helmi (Journal on Education, 2024)
The world of education in Indonesia, especially at the primary and secondary education levels, is faced with the most important and fundamental educational problem, namely the low quality of education. Various observations and analyzes were carried out, resulting in the conclusion that there are more or less three factors that cause the quality of education in Indonesia to not experience significant improvement, namely: the implementation of education in Indonesia uses an "Educational Function" or "input-output analysis" approach which is not carried out consistently. Consequently, the implementation of education is centralized bureaucratic, so that schools are very dependent on bureaucratic decisions and minimal community participation. One of the managerial strategies developed to ensure that a school organization has resilience and vitality in the present and is sustainable into the future is by carrying out a SWOT analysis in order to formulate an organization, both a business company and a social organization. The method used in this research is a qualitative approach. This type of research is a library study or can be called a literature study, namely research that limits research activities to materials found in the library without doing any research.